Exploitation of the far-offshore wind energy resource by fleets of energy ships. Part A. Energy ship design and performance - Babarit, Aurélien; Clodic, Gaël; Delvoye, Simon; Gilloteaux, Jean-Christophe (HAL CCSD, 2020)
International audience This paper deals with a new concept for the conversion of far-offshore wind energy into sustainable fuel. It relies on autonomously sailing energy ships and manned support tankers. Energy ships are wind-propelled. They generate electricity using water turbines attached underneath their hull. Since energy ships are not grid-connected, they include onboard power-to-X plants for storage of the produced energy. In the present work, the energy vector is methanol. The aim of the paper is to propose an energy ship design and to provide an estimate for its energy performance as function of 10 the wind conditions. The energy performance assessment is based on a numerical model which is described in the paper. Results show that the wind energy-to-methanol (chemical energy) conversion efficiency is 24% and that such energy ship deployed in the North Atlantic Ocean could produce approximately 5 GWh per annum of chemical energy (900 tonnes of methanol per annum).